Diverse animal models for Chlamydia infections: unraveling pathogenesis through the genital and gastrointestinal tracts - Tian, Qi; Zhang, Tianyuan; Shu, Chuqiang; Han, Zixuan; Huang, Youyou; Wan, Jiao; Wang, Luying; Sun, Xin (Frontiers in Microbiology, 2024)
Chlamydia trachomatis is responsible for infections in various mucosal tissues, including the eyes, urogenital, respiratory, and gastrointestinal tracts. Chronic infections can result in severe consequences such as blindness, ectopic pregnancy, and infertility. The underlying mechanisms leading to these diseases involve sustained inflammatory responses, yet thorough comprehension of the underlying mechanisms remains elusive. Chlamydial biologists employ in multiple methods, integrating biochemistry, cell biology, and genetic tools to identify bacterial factors crucial for host cell interactions. While numerous animal models exist to study chlamydial pathogenesis and assess vaccine efficacy, selecting appropriate models for biologically and clinically relevant insights remains a challenge.Genital infection models in animals have been pivotal in unraveling host-microbe dynamics, identifying potential chlamydial virulence factors influencing genital pathogenicity. However, the transferability of this knowledge to human pathogenic mechanisms remains uncertain. Many putative virulence factors lack assessment in optimal animal tissue microenvironments, despite the diverse chlamydial infection models available. Given the propensity of genital Chlamydia to spread to the gastrointestinal tract, investigations into the pathogenicity and immunological impact of gut Chlamydia become imperative. Notably, the gut emerges as a promising site for both chlamydial infection vaccination and pathogenesis. This review elucidates the pathogenesis of Chlamydia infections and delineates unique features of prevalent animal model systems. The primary focus of this review is to consolidate and summarize current animal models utilized in Chlamydia researches, presenting findings, discussions on their contributions, and suggesting potential directions for further studies.